Techno-Economic Feasibility of Small Scale Hydropower in Ethiopia: The Case of the Kulfo River, in Southern Ethiopia - Girma, Zelalem (Journal of Renewable Energy, 2016)
This paper presents the technical and economic feasibility of grid connected small scale hydropower construction in selected site of the Kulfo River in southern Ethiopia. In doing so the paper presents the general overview of Ethiopia electric power situation; small scale hydropower situation and barriers and drivers for its development; site assessment and cost estimation methods and at the end presents techno-economic analysis of small scale hydropower development on the Kulfo River in southern Ethiopia. The technical and economic feasibility of the site have been studied by using HOMER, RETscreen, and SMART Mini-IDRO software. The result of simulation shows that the construction of small scale hydropower in the Kulfo River is technically and economically feasible with total net present cost of $13,345,150, cost of energy $0.028/kWh, simple payback period of 12.4 year, and internal rate of return 12.9%. The result also shows that construction of hydropower curtails greenhouse gas emissions such as carbon dioxide by 96,685,45 kg/year, sulfur dioxide by 4,1917 kg/year, and nitrogen dioxide by 20,500 kg/year.